Maman Fish Sdn. Bhd. / Azizi Azuan Abu Bakar ... [et al.] - Abu Bakar, Azizi Azuan; Musa, Azham; Minhat, Mohd. Asrul; Kamisan, Mohd. Nazri; Sariau, Jaslinah (Faculty of Mechanical Engineering, 2003)
Maman Fish Sdn. Bhd. is the name of our company that has decided to make business in cages fish. This company is a private limited business. Actually, to get involved in this type of business is not quite easy. This is because the cost to do this business is high. In cages fish, we must need at least RM 3.3 million to run this kind of business. For certain people, said that it is a risky one, but for us it is an opportunity that will give us a large amount of profit.